Efektivitas Pendampingan dalam Produksi dan Pengunaan Insektisida Organik di Kelompok Tani Sumber Urip Malang - Moch. Agus Krisno Budiyanto; Muizuddin Muizuddin; Samsun Hadi (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2016)
Indonesia has the potential huge vegetable in the production of organic insecticide. In many areas still needed assistance to the farmer groups to produce and use organic insecticide. The objective of this study was to determine the effectiveness of assistance in the production and use of organic insecticides  in Farmers Group Sumber Urip Malang. The design study is cross sectional. Assistance performed 10 times in the production and use of organic insecticides involving 10 Farmers Group Sumber Urip I and 10 Farmers Group Sumber Urip II. Before the assistance do is the pretest and after the assistance do is posttest to knowing the knowledge and skills in the production and use of organic insecticides. Data collection method used was a questionnaire, observation, and interviews, while the method of data analysis used is the paired t-test. The results showed that; 1) there is a significant difference of knowledge production of organic insecticide before and after assistance (t-hit> t-tab0,01, 7.259 > 2.861), 2) there are significant differences of organic insecticide production skills before and after assistance (t-hit > t-tab0,01, 10.057 > 2.861), 3) there are significant differences knowledge of the use of organic insecticides before and after assistance (t-hit > t-tab0,01, 8.731 > 2.861), and 4) there are differences significant organic insecticide usage skills before and after assistance (t-hit > t-tab0,01, 8.028 > 2.861). From the results of such research can be summed up the results of research that effective assistance to increase skills and knowledge production and use of organic insecticides.